Relationships between Levels of Knowledge and Attitude towards Behavior of Using Personal Protective Equipment among Professional Students at RSGM Baiturrahmah during COVID-19 Pandemic - Nada H. Salsabila; Abu Bakar; Ricky Amran; Valendriyani Ningrum (Universitas Sam Ratulangi, 2022)
Abstract: Coronavirus disease 2019 (COVID-19) is a respiratory infection that can cause serious respiratory problems. Several studies stated that the levels of knowledge and attitude about personal protective equipment (PPE) can affect the behavior of using PPE. This study aimed to identify the relationships between levels of knowledge and attitude towards behavior of using PPE among students of the professional stage at RSGM Baiturrahmah during the COVID-19 pandemic. This was a quantitative study using an observational and analytical method with a cross sectional design. There were 85 respondents obtained by accidental sampling in this study. Data were collected by giving questionnaires to the respondents. The results showed that most respondents (94.1%) had levels of knowledge, attitude, and behavior of good category. The statistics analyses showed that there were significant relationships between the levels of knowledge and attitude towards behavior of using PPE (p<0.05). In conclusion, there are relationships between the levels of knowledge and attitude towards behavior of using PPE among students at the professional stage at RSGM Baiturrahmah during the COVID-19 pandemic.Keywords: personal protective equipment; knowledge; attitude; behavior; COVID-19Â Abstrak: Coronavirus 2019 (COVID-19) merupakan infeksi saluran pernapasan yang dapat menyebabkan masalah pernapasan serius. Beberapa penelitian menyatakan bahwa tingkat pengetahuan dan sikap tentang alat pelindung diri (APD) dapat memengaruhi perilaku penggunaan APD. Penelitian ini bertujuan untuk mengidentifikasi hubungan antara tingkat pengetahuan dan sikap terhadap perilaku penggunaan APD mahasiswa tahap profesi di RSGM Baiturrahmah pada masa pandemi COVID-19. Jenis penelitian ialah kuantitatif dengan pendekatan metode analitik observasional dan desain potong lintang. Hasil penelitian mendapatkan 85 responden yang diambil secara accidental sampling. Pengambilan data dilakukan dengan memberikan kuesioner kepada responden. Sebagian besar responden (94,1%) memiliki tingkat pengetahuan, sikap, dan perilaku dengan kategori baik. Hasil uji statistik menunjukkan adanya hubungan bermakna antara tingkat pengetahuan dan sikap terhadap perilaku penggunaan APD, masing-masing dengan nilai p<0,05. Simpulan penelitian ini ialah terdapat hubungan bermakna antara tingkat pengetahuan dan sikap terhadap perilaku penggunaan APD pada mahasiswa tahap profesi di RSGM Baiturrahmah di masa pandemi COVID-19.Kata kunci: alat pelindung diri; pengetahuan; sikap; perilaku; COVID-19